The Effect of Implementation of Independent Curriculum on Motivation and Performance of Biology Teachers in Public High Schools - Abdul Ashari; Amalia Buntu; Rafiqah; Nurul Afiat (Postgraduate, University of Mataram, 2025)
The Independent Curriculum is an educational innovation aimed at providing schools with the flexibility to determine an educational model that fits local needs and the characteristics of students. This study aims to describe the impact of the implementation of the Independent Curriculum on the motivation and performance of biology teachers in public high schools in Palu City. This is a descriptive study with a quantitative approach, to be conducted in 10 public high schools across Palu City. The sample consists of 20 biology teachers from these high schools. The instrument used in the study is an open-ended questionnaire on three aspects: the implementation of the Independent Curriculum, motivation, and performance. For the implementation aspect, there are 16 questions from 3 indicators, for motivation there are 16 questions from 2 indicators, and for performance there are 27 questions from 3 indicators. Tests for validity and reliability, normalcy, linearity, and hypothesis testing with Simple Regression Analysis are all included in the study. Based on the research findings and hypothesis testing, it can be concluded that the implementation of the independent curriculum has a significant and positive effect on the motivation and performance of biology teachers in public high schools in Palu City, with a significance value of 0.000, where <0.05. Furthermore, the results acquired might be used as a foundation for studies on the biology education process under Independent Curriculum.